Flame-retardant antistatic wear-resistant fabric and preparation method thereof
The reaction of modified nano titanium dioxide, modified polyester and pyrrole is made of flame retardant and anti-static wear-resistant fabrics, which solves the problems of flammability and electrostatic accumulation of polyester textiles, and improves the flame retardant, anti-static and wear-resistant properties of the fabrics , ensuring higher safety and service life.
Patent Information
- Application Number
- CN202411273201.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
Polyester textiles are flammable, electrostatic accumulation and wear resistance, resulting in safety hazards and degradation of performance.
The modified nanotitanium dioxide, modified polyester and pyrrole mixture is reacted, and then spinned and woven to produce flame-retardant and anti-static wear-resistant fabrics. The phosphoric acid generation and flame-retardant effect of nanotitanium dioxide are produced by the physical adsorption and antibacterial effect of polyester. , and the conductive and sterilizing effects of pyrrole improve the flame retardant, antistatic and wear resistance of fabrics.
It significantly improves the flame retardant ability, antistatic properties and wear resistance of the fabric, increases the limit oxygen index, bacteriostatic rate and fracture retention rate, and reduces the surface resistivity, ensuring higher safety and service life.
Smart Images

Figure BDA0005039342080000071 
Figure BDA0005039342080000091 
Figure BDA0005039342080000101
Abstract
Description
Technical Field
[0001] The invention relates to the field of fabrics, in particular to a flame-retardant, antistatic, and wear-resistant fabric and a preparation method thereof. Background Art
[0002] Polyester is a linear polymer obtained by esterification or exchange and polycondensation of terephthalic acid and ethylene glycol, and then a synthetic fiber fabric obtained by a series of processing techniques such as melt spinning and weaving. Polyester is currently the world's largest-produced and most widely used synthetic fiber. It has many excellent practical properties such as strong wear resistance, good resilience, good wrinkle resistance, good heat resistance, solidity and durability. It is widely used in clothing manufacturing, decorative items, automotive interiors, industrial textiles and other special-purpose textiles.
[0003] However, there is no flame retardant element in the molecular structure of polyester. The limiting oxygen index of polyester fabric is generally about 19 to 22, which is a flammable material. It is easy to be ignited when encountering flames, and a large amount of heat and molten droplets with flames will be released during the combustion process, which is easy to cause the rapid spread of fire and secondary burns to people or animals, bringing great threats to people's life and property safety. In addition, the polyester molecular structure lacks hydrophilic groups and has significant hydrophobicity, so that when the textiles made of polyester are subjected to the effects of friction, contact and other forms, static electricity is easily generated on the surface and electric charges are accumulated, and heat and temperature gradients are also generated, which leads to new problems such as fiber softening, creep, and mechanical property degradation, and aggravates the generation of static charge, which brings serious harm and safety hazards to the production, processing and application of polyester textiles. Therefore, the present invention develops an antistatic wear-resistant fabric with flame retardant ability. Summary of the invention
[0004] In view of the deficiencies in the prior art, the technical problem that the present invention intends to solve is to provide a flame retardant, antistatic, and wear-resistant fabric and a preparation method thereof to solve the problems existing in the prior art.
[0005] The technical solution of the present invention to solve the technical problem of the fabric is to provide a flame retardant, antistatic and wear-resistant fabric, wherein the flame retardant, antistatic and wear-resistant fabric is prepared by reacting a mixed solution of modified polyester, modified nano titanium dioxide and pyrrole, and then spinning and weaving;
[0006] The modified nano titanium dioxide is prepared by reacting nano titanium dioxide with 3-aminopropyltrimethoxysilane, 2,5-dihydroxyterephthalaldehyde and 1-aminopyrrole in sequence;
[0007] The modified polyester is prepared by reacting an ester mixed solution with an alcohol mixed solution and then reacting the mixed solution with 1-allyl-1H-pyrrole.
[0008] The technical solution of the present invention to solve the technical problem of the method is to provide a method for preparing a flame retardant, antistatic and wear-resistant fabric, and the method for preparing the flame retardant, antistatic and wear-resistant fabric mainly includes the following preparation steps:
[0009] (1) mixing amino nano-titanium dioxide, 2,5-dihydroxyterephthalaldehyde and ethanol in a mass ratio of 1:1.3-1.5:10-12, stirring at 200-300 r / min for 30-50 min, filtering, washing with ethanol for 3-5 times, and drying at 70-80° C. for 5-7 h to obtain pre-modified nano-titanium dioxide;
[0010] (2) pre-modified nano titanium dioxide, 1-aminopyrrole and ethanol are mixed in a mass ratio of 1:1.3-1.5:10-12, stirred at 200-300 r / min for 30-50 min, filtered, washed with ethanol for 3-5 times, and dried at 70-80° C. for 5-7 h to obtain modified nano titanium dioxide;
[0011] (3) Mixing the ester mixed solution, the alcohol mixed solution and sodium acetate in a mass ratio of 1:1:0.06-0.1, stirring at 210-220°C, under nitrogen protection, at 200-300 r / min for 10-12 hours, and cooling to room temperature to obtain a pre-modified polyester; mixing the pre-modified polyester and 1-allyl-1H-pyrrole in a mass ratio of 1:0.1-0.12, placing in a high-pressure reactor, reacting at 115-125°C for 10-12 hours, washing with ethanol for 3-5 times, and drying at 70-80°C for 22-24 hours to obtain a modified polyester;
[0012] (4) Modified polyester, modified nano-titanium dioxide, pyrrole mixed solution, ferric chloride, ethanol and deionized water are mixed in a mass ratio of 8-10:1-3:1.5-2.5:0.2-0.26:6-10:30-34, stirred at 50-70°C and 200-300 r / min for 20-30 min, and then dried at 40-60°C for 22-26 h to obtain modified polyester, and the modified polyester is spun and woven to obtain flame-retardant, antistatic and wear-resistant fabrics.
[0013] As an optimization, the amino-modified nano-titanium dioxide in step (1) is prepared by uniformly mixing nano-titanium dioxide, 3-aminopropyltrimethoxysilane and isopropanol in a mass ratio of 1:1:6-8, stirring and reacting at 85-95°C and 200-300 r / min for 5-7 hours, centrifuging, washing with deionized water for 3-5 times, and drying at 90-100°C for 2-4 hours.
[0014] As an optimization, the ester mixture in step (3) is prepared by uniformly mixing dimethyl phosphite and dimethyl terephthalate in a mass ratio of 1:3 to 5.
[0015] As an optimization, the alcohol mixture in step (3) is prepared by uniformly mixing 1,5-pentanediol and tri(3-hydroxypropyl)amine in a mass ratio of 3 to 5:1.
[0016] As an optimization, the pyrrole mixture in step (4) is prepared by uniformly mixing bromopropylpyrrole and pyrrole in a mass ratio of 1:3 to 5.
[0017] As an optimization, the spinning method in step (4) is melt electrospinning; the spinning parameters are: temperature 260-280°C, discharge diameter 0.8-1.2mm, spinning voltage 26-30KV, and receiving distance 16-18cm.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] When preparing the flame-retardant, antistatic and wear-resistant fabric, the present invention sequentially reacts nano titanium dioxide with 3-aminopropyltrimethoxysilane, 2,5-dihydroxyterephthalaldehyde and 1-aminopyrrole to obtain modified nano titanium dioxide; reacts an ester mixed solution with an alcohol mixed solution and then reacts with 1-allyl-1H-pyrrole to obtain modified polyester; and reacts the modified polyester, the modified nano titanium dioxide and the pyrrole mixed solution, and then spins and weaves to obtain the flame-retardant, antistatic and wear-resistant fabric.
[0020] Firstly, nano titanium dioxide is reacted with 3-aminopropyltrimethoxysilane, 2,5-dihydroxyterephthalaldehyde and 1-aminopyrrole in sequence to obtain modified nano titanium dioxide; titanium dioxide has a high specific surface area and can effectively adsorb and fix microorganisms on the surface. The physical adsorption can prevent the normal growth and reproduction of microorganisms, interfere with the growth cycle of bacteria, destroy their biofilm structure, further inhibit the growth and reproduction of bacteria, and make the prepared fabric antibacterial; in addition, titanium dioxide can also enhance the wear resistance of fibers; aminated nano titanium dioxide can form a structure that can absorb ultraviolet light with 2,5-dihydroxyterephthalaldehyde to achieve anti-aging effects.
[0021] Secondly, the ester mixed liquid and the alcohol mixed liquid are reacted and then reacted with 1-allyl-1H-pyrrole to obtain modified polyester; the phosphorus contained in the polyester can generate phosphorus-containing free radicals, which can capture hydrogen free radicals and hydroxyl free radicals in the flame area, interrupt the polymer combustion chain reaction and thus slow down the combustion, and can generate polymetaphosphoric acid with a stable structure and low volatility during the combustion process. The polymetaphosphoric acid has a strong dehydration effect, and during the heating process, the polymer is carbonized into a dense and flame-retardant carbonized layer, and the carbonized layer covers the surface of the polymer, isolates the bottom material from contact with external oxygen, and hinders the external heat from being transferred to the base material, thereby effectively preventing the material from further pyrolysis and terminating the combustion of the material, thereby improving the flame retardancy of the material.
[0022] Finally, the modified polyester, modified nano titanium dioxide and pyrrole mixture are reacted, and then spun and woven to obtain flame-retardant, antistatic and wear-resistant fabrics; bromopropyl pyrrole in the pyrrole mixture can react with tri(3-hydroxypropyl)amine to form quaternary ammonium salts, which can kill bacteria by destroying cell membranes, inhibiting enzyme activity and destroying nucleic acids. These mechanisms make quaternary ammonium salts an effective bactericide, and have a killing effect on a wide spectrum of bacteria, fungi and some viruses, thereby achieving an antibacterial effect; in addition, quaternary ammonium salts can also absorb moisture in the air, which helps to reduce the resistivity of the material surface; the modified polyester, modified nano titanium dioxide and pyrrole mixture can react to generate polypyrrole, which, as a conductive polymer, can absorb and disperse static charge, thereby reducing the accumulation of static electricity and achieving an antistatic effect, and polypyrrole can produce non-flammable gas, which can dilute the concentration of oxygen in the air and combustibles produced by thermal decomposition of polymers on the one hand, and the nitrogen oxides produced by decomposition on the other hand can capture free radicals, inhibit the chain reaction of polymers, and improve the flame retardant ability of the material. DETAILED DESCRIPTION
[0023] The specific embodiments of the present invention are given below. The specific embodiments are only used to further illustrate the present invention in detail and do not limit the protection scope of the present invention.
[0024] Example 1
[0025] A method for preparing a flame-retardant, antistatic and wear-resistant fabric mainly comprises the following preparation steps:
[0026] (1) Aminated nano-titanium dioxide, 2,5-dihydroxyterephthalaldehyde and ethanol were mixed in a mass ratio of 1:1.3:10, stirred at 200 r / min for 30 min, filtered, washed with ethanol three times, and dried at 70° C. for 5 h to obtain pre-modified nano-titanium dioxide;
[0027] (2) pre-modified nano-titanium dioxide, 1-aminopyrrole and ethanol were mixed in a mass ratio of 1:1.3:10, stirred at 200 r / min for 30 min, filtered, washed with ethanol three times, and dried at 70° C. for 5 h to obtain modified nano-titanium dioxide;
[0028] (3) The ester mixed solution, the alcohol mixed solution and sodium acetate were mixed in a mass ratio of 1:1:0.06, stirred at 210°C, under nitrogen protection, and 200 r / min for 10 hours, and cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester and 1-allyl-1H-pyrrole were mixed in a mass ratio of 1:0.1, placed in a high-pressure reactor, reacted at 115°C for 10 hours, washed with ethanol three times, and dried at 70°C for 22 hours to obtain a modified polyester;
[0029] (4) Modified polyester, modified nano-titanium dioxide, pyrrole mixed solution, ferric chloride, ethanol and deionized water were mixed in a mass ratio of 8:1:1.5:0.2:6:30, stirred at 50°C and 200 r / min for 20 min, and then dried at 40°C for 22 h to obtain modified polyester. The modified polyester was spun and woven to obtain flame-retardant, antistatic and wear-resistant fabrics.
[0030] Example 2
[0031] A method for preparing a flame-retardant, antistatic and wear-resistant fabric mainly comprises the following preparation steps:
[0032] (1) Aminated nano-titanium dioxide, 2,5-dihydroxyterephthalaldehyde and ethanol were mixed in a mass ratio of 1:1.4:11, stirred at 250 r / min for 40 min, filtered, washed with ethanol 4 times, and dried at 75° C. for 6 h to obtain pre-modified nano-titanium dioxide;
[0033] (2) pre-modified nano-titanium dioxide, 1-aminopyrrole and ethanol were mixed in a mass ratio of 1:1.4:11, stirred at 250 r / min for 40 min, filtered, washed with ethanol 4 times, and dried at 75° C. for 6 h to obtain modified nano-titanium dioxide;
[0034] (3) The ester mixture, the alcohol mixture and sodium acetate were mixed in a mass ratio of 1:1:0.08, stirred at 215°C, under nitrogen protection, and 250 r / min for 11 hours, and cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester and 1-allyl-1H-pyrrole were mixed in a mass ratio of 1:0.11, placed in a high-pressure reactor, reacted at 120°C for 11 hours, washed with ethanol 4 times, and dried at 75°C for 23 hours to obtain a modified polyester;
[0035] (4) Modified polyester, modified nano-titanium dioxide, pyrrole mixed solution, ferric chloride, ethanol and deionized water were mixed in a mass ratio of 9:2:2:0.23:8:32, stirred at 60°C and 250 r / min for 25 min, and then dried at 50°C for 24 h to obtain modified polyester. The modified polyester was spun and woven to obtain flame-retardant, antistatic and wear-resistant fabrics.
[0036] Example 3
[0037] A method for preparing a flame-retardant, antistatic and wear-resistant fabric mainly comprises the following preparation steps:
[0038] (1) Aminated nano-titanium dioxide, 2,5-dihydroxyterephthalaldehyde and ethanol were mixed in a mass ratio of 1:1.5:12, stirred at 300 r / min for 50 min, filtered, washed with ethanol for 5 times, and dried at 80° C. for 7 h to obtain pre-modified nano-titanium dioxide;
[0039] (2) pre-modified nano-titanium dioxide, 1-aminopyrrole and ethanol were mixed in a mass ratio of 1:1.5:12, stirred at 300 r / min for 50 min, filtered, washed with ethanol for 5 times, and dried at 80° C. for 7 h to obtain modified nano-titanium dioxide;
[0040] (3) The ester mixture, the alcohol mixture and sodium acetate were mixed in a mass ratio of 1:1:0.1, stirred at 220°C, under nitrogen protection, and 300 r / min for 12 hours, and cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester and 1-allyl-1H-pyrrole were mixed in a mass ratio of 1:0.12, placed in a high-pressure reactor, reacted at 125°C for 12 hours, washed with ethanol 5 times, and dried at 80°C for 24 hours to obtain a modified polyester;
[0041] (4) Modified polyester, modified nano-titanium dioxide, pyrrole mixed solution, ferric chloride, ethanol and deionized water were mixed in a mass ratio of 10:3:2.5:0.26:10:34, stirred at 70°C and 300 r / min for 30 min, and then dried at 60°C for 26 h to obtain modified polyester. The modified polyester was spun and woven to obtain flame-retardant, antistatic and wear-resistant fabrics.
[0042] Comparative Example 1
[0043] A method for preparing a flame-retardant, antistatic and wear-resistant fabric mainly comprises the following preparation steps:
[0044] (1) The ester mixed solution, the alcohol mixed solution and sodium acetate were mixed in a mass ratio of 1:1:0.08, stirred at 215°C, under nitrogen protection, and 250 r / min for 11 hours, and cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester and 1-allyl-1H-pyrrole were mixed in a mass ratio of 1:0.11, placed in a high-pressure reactor, reacted at 120°C for 11 hours, washed with ethanol 4 times, and dried at 75°C for 23 hours to obtain a modified polyester;
[0045] (2) Modified polyester, nano-titanium dioxide, pyrrole mixed solution, ferric chloride, ethanol and deionized water were mixed in a mass ratio of 9:2:2:0.23:8:32, stirred at 60°C and 250 r / min for 25 min, and then dried at 50°C for 24 h to obtain modified polyester. The modified polyester was spun and woven to obtain flame-retardant, antistatic and wear-resistant fabrics.
[0046] Comparative Example 2
[0047] A method for preparing a flame-retardant, antistatic and wear-resistant fabric mainly comprises the following preparation steps:
[0048] (1) The ester mixed solution, the alcohol mixed solution and sodium acetate were mixed in a mass ratio of 1:1:0.08, stirred at 215°C, under nitrogen protection, and 250 r / min for 11 hours, and cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester and 1-allyl-1H-pyrrole were mixed in a mass ratio of 1:0.11, placed in a high-pressure reactor, reacted at 120°C for 11 hours, washed with ethanol 4 times, and dried at 75°C for 23 hours to obtain a modified polyester;
[0049] (2) The modified polyester, pyrrole mixed solution, ferric chloride, ethanol and deionized water were mixed in a mass ratio of 9:2:0.23:8:32, stirred at 60°C and 250 r / min for 25 min, and then dried at 50°C for 24 h to obtain the modified polyester. The modified polyester was spun and woven to obtain a flame retardant, antistatic and wear-resistant fabric.
[0050] Comparative Example 3
[0051] A method for preparing a flame-retardant, antistatic and wear-resistant fabric mainly comprises the following preparation steps:
[0052] (1) Aminated nano-titanium dioxide, 2,5-dihydroxyterephthalaldehyde and ethanol were mixed in a mass ratio of 1:1.4:11, stirred at 250 r / min for 40 min, filtered, washed with ethanol 4 times, and dried at 75° C. for 6 h to obtain pre-modified nano-titanium dioxide;
[0053] (2) pre-modified nano-titanium dioxide, 1-aminopyrrole and ethanol were mixed in a mass ratio of 1:1.4:11, stirred at 250 r / min for 40 min, filtered, washed with ethanol 4 times, and dried at 75° C. for 6 h to obtain modified nano-titanium dioxide;
[0054] (3) The ester mixture, the alcohol mixture and sodium acetate were mixed in a mass ratio of 1:1:0.08, stirred at 215°C, under nitrogen protection, and 250 r / min for 11 hours, and cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester and 1-allyl-1H-pyrrole were mixed in a mass ratio of 1:0.11, placed in a high-pressure reactor, reacted at 120°C for 11 hours, washed with ethanol 4 times, and dried at 75°C for 23 hours to obtain a modified polyester;
[0055] (4) Modified polyester, modified nano-titanium dioxide, pyrrole, ferric chloride, ethanol and deionized water were mixed in a mass ratio of 9:2:2:0.23:8:32, stirred at 60°C and 250 r / min for 25 min, and then dried at 50°C for 24 h to obtain modified polyester. The modified polyester was spun and woven to obtain flame-retardant, antistatic and wear-resistant fabrics.
[0056] Comparative Example 4
[0057] A method for preparing a flame-retardant, antistatic and wear-resistant fabric mainly comprises the following preparation steps:
[0058] (1) Aminated nano-titanium dioxide, 2,5-dihydroxyterephthalaldehyde and ethanol were mixed in a mass ratio of 1:1.4:11, stirred at 250 r / min for 40 min, filtered, washed with ethanol 4 times, and dried at 75° C. for 6 h to obtain pre-modified nano-titanium dioxide;
[0059] (2) pre-modified nano-titanium dioxide, 1-aminopyrrole and ethanol were mixed in a mass ratio of 1:1.4:11, stirred at 250 r / min for 40 min, filtered, washed with ethanol 4 times, and dried at 75° C. for 6 h to obtain modified nano-titanium dioxide;
[0060] (3) dimethyl terephthalate, alcohol mixture and sodium acetate were mixed in a mass ratio of 1:1:0.08, stirred at 215°C, under nitrogen protection, and 250 r / min for 11 hours, and cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester and 1-allyl-1H-pyrrole were mixed in a mass ratio of 1:0.11, placed in a high-pressure reactor, reacted at 120°C for 11 hours, washed with ethanol 4 times, and dried at 75°C for 23 hours to obtain a modified polyester;
[0061] (4) Modified polyester, modified nano-titanium dioxide, pyrrole mixed solution, ferric chloride, ethanol and deionized water were mixed in a mass ratio of 9:2:2:0.23:8:32, stirred at 60°C and 250 r / min for 25 min, and then dried at 50°C for 24 h to obtain modified polyester. The modified polyester was spun and woven to obtain flame-retardant, antistatic and wear-resistant fabrics.
[0062] Comparative Example 5
[0063] A method for preparing a flame-retardant, antistatic and wear-resistant fabric mainly comprises the following preparation steps:
[0064] (1) Aminated nano-titanium dioxide, 2,5-dihydroxyterephthalaldehyde and ethanol were mixed in a mass ratio of 1:1.4:11, stirred at 250 r / min for 40 min, filtered, washed with ethanol 4 times, and dried at 75° C. for 6 h to obtain pre-modified nano-titanium dioxide;
[0065] (2) pre-modified nano-titanium dioxide, 1-aminopyrrole and ethanol were mixed in a mass ratio of 1:1.4:11, stirred at 250 r / min for 40 min, filtered, washed with ethanol 4 times, and dried at 75° C. for 6 h to obtain modified nano-titanium dioxide;
[0066] (3) The ester mixture, the alcohol mixture and sodium acetate were mixed in a mass ratio of 1:1:0.08, stirred at 215°C, under nitrogen protection, and 250 r / min for 11 hours, and cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester and 1-allyl-1H-pyrrole were mixed in a mass ratio of 1:0.11, placed in a high-pressure reactor, reacted at 120°C for 11 hours, washed with ethanol 4 times, and dried at 75°C for 23 hours to obtain a modified polyester;
[0067] (4) The modified polyester and modified nano titanium dioxide are mixed in a mass ratio of 9:2, spun and woven to obtain a flame retardant, antistatic and wear-resistant fabric.
[0068] Test Example 1
[0069] Flame retardancy test
[0070] The limiting oxygen index was tested according to GBT / 2406 test standard. The results are shown in Table 1.
[0071] Table 1
[0072] Limiting oxygen index Example 1 32.5% Example 2 32.9% Example 3 32.3% Comparative Example 1 32.7% Comparative Example 2 32.1% Comparative Example 3 32.4% Comparative Example 4 28.6% Comparative Example 5 27.9%
[0073] From the comparison of the experimental data in Table 1, it can be found that the flame retardant, antistatic and wear-resistant fabric prepared by the present invention has good flame retardant ability.
[0074] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4 in Table 1, it can be found that the limiting oxygen index of Examples 1, 2, and 3 is larger than that of Comparative Example 4, which indicates that the phosphorus contained in the polyester can generate phosphorus-containing free radicals, which can capture hydrogen free radicals and hydroxyl free radicals in the flame area, interrupt the polymer combustion chain reaction to slow down the combustion, and generate polymetaphosphoric acid with a stable structure and low volatility during the combustion process. Polymetaphosphoric acid has a strong dehydration effect, which promotes the carbonization of the polymer into a dense and flame-retardant carbonized layer during the heating process. The carbonized layer covers the surface of the polymer, isolates the bottom material from the contact with the external oxygen, and hinders the external heat from being transferred to the base material, thereby effectively preventing the material from further pyrolysis and terminating the combustion of the material, improving the flame retardancy of the material, and increasing the limiting oxygen index of the material;
[0075] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 5, which shows that polypyrrole can produce non-combustible gas, which can dilute the concentration of oxygen in the air and combustibles produced by thermal decomposition of the polymer on the one hand, and the nitrogen oxides produced by decomposition can capture free radicals, inhibit the chain reaction of the polymer, improve the flame retardancy of the material, and increase the limiting oxygen index of the material.
[0076] Test Example 2
[0077] Antimicrobial testing
[0078] The test was carried out according to the GB / T20944 oscillation method, wherein the selected bacteria species were Staphylococcus aureus and Escherichia coli. The results are shown in Table 2.
[0079] Table 2
[0080]
[0081] From the comparison of the experimental data in Table 2, it can be found that the flame retardant, antistatic and wear-resistant fabric prepared by the present invention has good antibacterial ability.
[0082] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 2, it can be found that the antibacterial rates of Examples 1, 2, and 3 are higher than those of Comparative Example 2, which shows that titanium dioxide has a higher specific surface area and can effectively adsorb and fix microorganisms on the surface. This physical adsorption can prevent the normal growth and reproduction of microorganisms, thereby achieving the purpose of antibacterial. In addition, titanium dioxide can also interfere with the growth cycle of bacteria, destroy its biofilm structure, and further inhibit the growth and reproduction of bacteria, thereby achieving the effect of inhibiting and killing bacteria.
[0083] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the antibacterial rates of Examples 1, 2, 3 are higher than those of Comparative Example 3, which shows that quaternary ammonium salts can kill bacteria by destroying cell membranes, inhibiting enzyme activity and destroying nucleic acids. These mechanisms make quaternary ammonium salts an effective bactericide and have a killing effect on a wide spectrum of bacteria, fungi and some viruses, thereby achieving an antibacterial effect.
[0084] Test Example 3
[0085] Anti-aging test
[0086] Anti-aging test: Take the fiber before it is woven into fabrics for artificial accelerated light aging test. According to ISO4892-3 international standard, use fluorescent ultraviolet lamp UV-A340. After 15 days of irradiation, use YG061F electronic single yarn strength tester to test the tensile strength of the fiber. The test standard is GB / T14344. Calculate the tensile fracture retention rate, where tensile fracture retention rate = tensile fracture strength after aging treatment / tensile fracture strength before aging treatment * 100%. The results are shown in Table 3.
[0087] Table 3
[0088] Tensile break retention rate Example 1 98.1% Example 2 97.9% Example 3 98.3% Comparative Example 1 95.1% Comparative Example 2 94.9% Comparative Example 3 98.2% Comparative Example 4 98.0% Comparative Example 5 97.9%
[0089] From the comparison of the experimental data in Table 3, it can be found that the flame retardant, antistatic and wear-resistant fabric prepared by the present invention has good anti-aging ability.
[0090] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 3, it can be found that the fracture retention rates of Examples 1, 2, 3 are greater than those of Comparative Example 1, which indicates that the amino-treated nano-titanium dioxide can form a structure that can absorb ultraviolet light with 2,5-dihydroxyterephthalaldehyde to achieve an anti-aging effect.
[0091] Test Example 4
[0092] Wear test
[0093] Wear test: The fiber wear test before being woven into fabrics was carried out using a reciprocating fiber wear tester. The diameter of the friction roller was 10 mm, and the surface was covered with W20 (02) metallographic sandpaper. The abrasive material on the sandpaper surface was silicon carbide, and the corresponding abrasive size was 20 μm. The reciprocating distance was 25 mm, the reciprocating frequency was 95 times / min, and the fiber tension was 0.45 cN·dtex. -1 The fiber-coated friction roller has a coating angle of 110°, the test environment temperature is 25°C, and the humidity is 60%. The reciprocating times of the friction roller from the start of the fiber wear resistance test to the fiber wear and fracture failure are defined as the maximum friction times of the fiber. The results are shown in Table 4.
[0094] Table 4
[0095] Maximum friction times Example 1 113 Example 2 115 Example 3 110 Comparative Example 1 111 Comparative Example 2 82 Comparative Example 3 114 Comparative Example 4 112 Comparative Example 5 110
[0096] From the comparison of the experimental data in Table 4, it can be found that the flame retardant, antistatic and wear-resistant fabric prepared by the present invention has good wear resistance.
[0097] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 4, it can be found that the maximum friction times of Examples 1, 2, 3 are greater than that of Comparative Example 2, which indicates that nano-titanium dioxide can enhance the wear resistance of the fiber.
[0098] Test Example 5
[0099] Antistatic test
[0100] The surface resistivity of the samples was measured using a surface resistance tester. The results are shown in Table 5.
[0101] Table 5
[0102]
[0103]
[0104] From the comparison of the experimental data in Table 5, it can be found that the flame retardant, antistatic and wear-resistant fabric prepared by the present invention has good antistatic ability.
[0105] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3 in Table 5, it can be found that the surface resistivity of Examples 1, 2, 3 is lower than that of Comparative Example 3, which shows that the quaternary ammonium salt has a hydrophilic group and can absorb moisture in the air. This hygroscopicity helps to reduce the resistivity of the material surface;
[0106] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5, it can be found that the surface resistivity of Examples 1, 2, 3 is lower than that of Comparative Example 5, which shows that polypyrrole, as a conductive polymer, can absorb and disperse static charges, thereby reducing the accumulation of static electricity, achieving an antistatic effect, and reducing the surface resistivity of the material.
[0107] Any matters not described in the present invention are applicable to the prior art.
Claims
1. A flame retardant, antistatic and wear-resistant fabric. It is characterized in that The flame-retardant, antistatic and wear-resistant fabric is prepared by reacting a mixed solution of modified polyester, modified nano titanium dioxide and pyrrole, and then spinning and weaving. The modified nano titanium dioxide is prepared by reacting nano titanium dioxide with 3-aminopropyltrimethoxysilane, 2,5-dihydroxyterephthalaldehyde and 1-aminopyrrole in sequence; The modified polyester is prepared by reacting an ester mixed solution with an alcohol mixed solution and then reacting the mixed solution with 1-allyl-1H-pyrrole.
2. A method for preparing a flame retardant, antistatic and wear-resistant fabric. It is characterized in that The preparation method of the flame-retardant, antistatic and wear-resistant fabric mainly includes the following preparation steps: (1) mixing amino nano-titanium dioxide, 2,5-dihydroxyterephthalaldehyde and ethanol in a mass ratio of 1:1.3-1.5:10-12, stirring at 200-300 r / min for 30-50 min, filtering, washing with ethanol for 3-5 times, and drying at 70-80° C. for 5-7 h to obtain pre-modified nano-titanium dioxide; (2) pre-modified nano titanium dioxide, 1-aminopyrrole and ethanol are mixed in a mass ratio of 1:1.3-1.5:10-12, stirred at 200-300 r / min for 30-50 min, filtered, washed with ethanol for 3-5 times, and dried at 70-80° C. for 5-7 h to obtain modified nano titanium dioxide; (3) Mixing the ester mixed solution, the alcohol mixed solution and sodium acetate in a mass ratio of 1:1:0.06-0.1, stirring at 210-220°C, under nitrogen protection, at 200-300 r / min for 10-12 hours, and cooling to room temperature to obtain a pre-modified polyester; mixing the pre-modified polyester and 1-allyl-1H-pyrrole in a mass ratio of 1:0.1-0.12, placing in a high-pressure reactor, reacting at 115-125°C for 10-12 hours, washing with ethanol for 3-5 times, and drying at 70-80°C for 22-24 hours to obtain a modified polyester; (4) Modified polyester, modified nano-titanium dioxide, pyrrole mixed solution, ferric chloride, ethanol and deionized water are mixed in a mass ratio of 8-10:1-3:1.5-2.5:0.2-0.26:6-10:30-34, stirred at 50-70°C and 200-300 r / min for 20-30 min, and then dried at 40-60°C for 22-26 h to obtain modified polyester, and the modified polyester is spun and woven to obtain flame-retardant, antistatic and wear-resistant fabrics.
3. The method for preparing a flame retardant, antistatic and wear-resistant fabric according to claim 2, It is characterized in that The amino-modified nano-titanium dioxide in step (1) is prepared by uniformly mixing nano-titanium dioxide, 3-aminopropyltrimethoxysilane and isopropanol in a mass ratio of 1:1:6-8, stirring at 85-95°C and 200-300 r / min for 5-7 hours, centrifuging, washing with deionized water for 3-5 times, and drying at 90-100°C for 2-4 hours.
4. The method for preparing a flame retardant, antistatic and wear-resistant fabric according to claim 2, It is characterized in that The ester mixed liquid in step (3) is prepared by uniformly mixing dimethyl phosphite and dimethyl terephthalate in a mass ratio of 1:3 to 5.
5. The method for preparing a flame retardant, antistatic and wear-resistant fabric according to claim 2, It is characterized in that The alcohol mixture in step (3) is prepared by uniformly mixing 1,5-pentanediol and tri(3-hydroxypropyl)amine in a mass ratio of 3 to 5:
1.
6. The method for preparing a flame retardant, antistatic and wear-resistant fabric according to claim 2, It is characterized in that The pyrrole mixed solution in step (4) is prepared by uniformly mixing bromopropyl pyrrole and pyrrole in a mass ratio of 1:3 to 5.
7. The method for preparing a flame retardant, antistatic and wear-resistant fabric according to claim 2, It is characterized in that The spinning method in step (4) is melt electrospinning; the spinning parameters are: temperature 260-280°C, discharge diameter 0.8-1.2mm, spinning voltage 26-30KV, and receiving distance 16-18cm.
Citation Information
Cited By
Ultraviolet light absorption antistatic fabric and preparation method thereof
CN119571519A
High-temperature-resistant and low-temperature-resistant plastic film and preparation method thereof
CN120484480A
High-temperature-resistant and low-temperature-resistant plastic film and preparation method thereof
CN120484480B
